MENGEMBANGKAN KEMAMPUAN KOGNITIF ANAK USIA DINI MELALUI PERMAINAN BALOK - AISYAH, AISYAH (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2020)
Cognitive as a thought process in the form of the ability to connect, assess and consider something. One of the cognitive abilities that children can develop is to recognize the concept of shape, color and size. Introducing the concept of shape, color, and size to children is important because color, shape and size are the most visible features in the world around us and can help children solve problems in life and adapt to their environment. There are 4 stages of child development, namely motor sensory, concrete pre-operation, concrete operation, and formal operation. Through play activities that contain education, children's thinking powers are stimulated to stimulate emotional, social and physical development. Utilizing the surrounding environment as a means and source of learning by giving children the opportunity to explore experiences gained orally or with creative media. The use of blocks in early childhood education is intended to develop various abilities of children, in addition to providing opportunities for children to explore. Educational game tools (APE) for early childhood are always designed with in-depth thinking tailored to the child's age range. Game tools for children aged 4-5 years are made simpler and not too difficult compared to games for children aged 5-6 years which are more difficult to work on.